Life in Conflict: A Series of Narratives by Locally Recruited Interpreters from Afghanistan - Maria Gomez-Amich (Close Encounters in War Journal, 2018)
Although irregular warfare (IW) is considered the oldest form of warfare, the war scenarios have considerably changed in the 21st century. Nowadays, IW seems to plague much of the non-Western world (White, Some Thoughts on Irregular Warfare) and, consequently, new actors, strategies and approaches have been brought into play, resulting into a new balance between State and Non-State organizations. Accordingly, and considering that “winning the war has ceased to mean only the annihilation of the enemy, but also transforming civilians into allies in the theatre of war” (Cumming, Influencing the Population: 43) collaborations between civilians and military personnel – based, among others, on new warfare tactics such as Petraeus’ Cultural Awareness concept – have been adopted. This may bring up, however, numerous concerns, including communication challenges when there is no common language. The interpreter in conflict zones (ICZ) funnels two or more realities in such contexts. This paper draws on five narrative interviews with five local ICZs from Afghanistan who supported and worked for the Spanish troops deployed in that country until the end of 2014. The main objective was to explore the life stories of these five locally-recruited interpreters who were born and raised a in a war-torn country, and to understand their perceptions regarding a series of aspects that, besides being closely related to their human nature – identity, culture, ideology and loyalty – tend to enhance, as per our initial hypothesis, the danger inherent in the local interpreter’s “otherness”, leading to a number of dilemmas including autonomous vs. heteronymous (see Cronin, The Empire Talks Back), civilian interpreter’s involvement vs. mistrust, or traditional enemy vs. irregular actors. The conclusions of this research study highlight a series of regularities among ICZs’ narratives with regard to how they experienced war, loyalty, and role as ICZs, all analysed from both the personal and the professional dimensions.